ANALISIS BRAND IMAGE THE COFFEE CAFE BANDAR LAMPUNG - Novita Sari (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
Brand (brand) is not only an important tool to attract consumers but also an intangible asset thatis important for the company to influence consumers in choosing a product. The Coffee cafe is one ofthe cafes in Lampung that provides food and drink which has a high taste.Based on the result of the research, it can be concluded that there are 13 attributes which formthe brand image of The Coffee Bandar Lampung in the minds of the community namely: Delightful taste,Original Coffee, The coffee scent, Famous or popular place, Strategic location, Clean, Narrow parkingarea, Safe place because there are many CCTV, Comfortable, Neat, Friendly Service, Fast Service, andAffordable Price.